2018
DOI: 10.18632/oncotarget.24620
|View full text |Cite
|
Sign up to set email alerts
|

Successful retreatment with grazoprevir and elbasvir for patients infected with hepatitis C virus genotype 1b, who discontinued prior treatment with NS5A inhibitor-including regimens due to adverse events

Abstract: BackgroundSustained virologic response (SVR) by interferon and interferon-free treatment can results in the reduction of advanced liver fibrosis and the occurrence of hepatocellular carcinoma in patients infected with hepatitis C virus (HCV). Recent interferon-free treatment for HCV shortens the duration of treatment and leads to higher SVR rates, without any serious adverse events. However, it is important to retreat patients who have had treatment-failure with HCV non-structural protein 5A (NS5A) inhibitor-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In some patients with HCV infection and severe renal impairment, treatment with DAAs is discontinued due to renal dysfunction [39]. For patients with CKD stages 4/5, hemodialysis should be prepared if renal function worsens and treatment with a DAA combination is initiated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some patients with HCV infection and severe renal impairment, treatment with DAAs is discontinued due to renal dysfunction [39]. For patients with CKD stages 4/5, hemodialysis should be prepared if renal function worsens and treatment with a DAA combination is initiated.…”
Section: Resultsmentioning
confidence: 99%
“…HCV infection is usually asymptomatic in patients with end-stage renal disease [ 38 ]; however, it may lead to decompensated liver diseases and HCC. In some patients with HCV infection and severe renal impairment, treatment with DAAs is discontinued due to renal dysfunction [ 39 ]. For patients with CKD stages 4/5, hemodialysis should be prepared if renal function worsens and treatment with a DAA combination is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this treatment is recommended in naïve patients or patients previously treated with interferon regimens, without cirrhosis or with compensated cirrhosis (Child A) and for 1 and 4 viral genotypes [ 26 ]. According to the C-EDGE TN and C-EDGE TE studies, another recommendation is established, since differences were observed in the sustained virologic response (SVR) rate based on the patient’s baseline viremia, it being adequate when it was less than 800,000 IU/mL [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main route of elimination of both drugs is biliary excretion. They present a minimal renal clearance, mainly detected in glecaprevir, although it is less than 1% (0.7%) [ 35 ]. “Glecaprevir/pibrentasvir” has been studied in patients with different degrees of kidney failure with and without dialysis and a 56% increase in AUC and was found not to be clinically significant [ 1 , 17 ].…”
Section: Resultsmentioning
confidence: 99%